2019
DOI: 10.3390/genes10121036
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Staphylococcus aureus Enterotoxin Gene Cluster Superantigens in Cystic Fibrosis Clinical Isolates

Abstract: Background: Staphylococcus aureus is a highly prevalent respiratory pathogen in cystic fibrosis (CF). It is unclear how this organism establishes chronic infections in CF airways. We hypothesized that S. aureus isolates from patients with CF would share common virulence properties that enable chronic infection. Methods: 77 S. aureus isolates were obtained from 45 de-identified patients with CF at the University of Iowa. We assessed isolates phenotypically and used genotyping assays to determine the presence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The superantigens induce T lymphocytes and antigen-presenting cells causing massive cytokine production, with lethal effects dependent on direct toxic and cytokine effects on the cardiovascular system 57 . Recent studies showed that egc -clustered enterotoxins are the most prevalent virulence factors in S. aureus isolated nowadays 27 , 46 , 58 . However, longitudinal studies are needed to better elucidate the role of locus egc in oral S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%
“…The superantigens induce T lymphocytes and antigen-presenting cells causing massive cytokine production, with lethal effects dependent on direct toxic and cytokine effects on the cardiovascular system 57 . Recent studies showed that egc -clustered enterotoxins are the most prevalent virulence factors in S. aureus isolated nowadays 27 , 46 , 58 . However, longitudinal studies are needed to better elucidate the role of locus egc in oral S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial superantigens that are produced by staphylococci and streptococci are phylogenetically classified into five groups, among which four groups (I, II, III, and V) include SEs and TSST-1 [3,4,6]. The prevalence of SE genes including sea-see and seg-selu in S. aureus has been analyzed in many studies of isolates from bacteremia [7,8], diabetic foot ulcers [9], cystic fibrosis [10], and colonization in healthy humans [11,12], as well as those from animals and the environment [13][14][15]. Although the distribution of SE genes sea-see and seg-seo (or -seu) to clinical isolates of HA-and CA-MRSA was also investigated previously [16][17][18], the prevalence of more recently described SE(-like) genes (sey, selw, selx, selz, sel26, and sel27) has not yet been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These six superantigens appear to be common in isolates, at least since 2008 (24). They appear to be more like colonization factors, as opposed to causing TSS (23,25).…”
Section: Discussionmentioning
confidence: 91%
“…TSST-1 is the exclusive cause of menstrual TSS, occurring with mucosal colonization of S. aureus ( 22 ). In recent studies, it has been shown that there has been a significant increase in stains producing the six-member enterotoxin gene cluster of superantigens, at least since 2008 ( 23 , 24 ). These six superantigens, including SEG and SE-like I, M, N, O, and U, appear to be more important for S. aureus colonization than overt disease causation ( 25 ).…”
Section: Introductionmentioning
confidence: 99%